2020
DOI: 10.3390/v12111342
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association of Socioeconomic Position with Microcephaly and Delayed Childhood Neurodevelopment among Children with Prenatal Zika Virus Exposure

Abstract: Increased rates of Zika virus have been identified in economically deprived areas in Brazil at the population level; yet, the implications of the interaction between socioeconomic position and prenatal Zika virus exposure on adverse neurodevelopmental outcomes remains insufficiently evaluated at the individual level. Using data collected between September 2015 and September 2019 from 163 children with qRT-PCR and/or IgM-confirmed prenatal exposure to Zika virus participating in a prospective cohort study in Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Multiple studies have identified socioeconomic drivers for neurodevelopmental disabilities. For instance, higher maternal education reduced the risk of microcephaly prior to the pandemic in Brazil [ 128 , 129 ]. Further, lower household income and higher crowding was a risk factor for microcephaly [ 56 , 129 ].…”
Section: Public Health Community and Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have identified socioeconomic drivers for neurodevelopmental disabilities. For instance, higher maternal education reduced the risk of microcephaly prior to the pandemic in Brazil [ 128 , 129 ]. Further, lower household income and higher crowding was a risk factor for microcephaly [ 56 , 129 ].…”
Section: Public Health Community and Environmental Factorsmentioning
confidence: 99%
“…For instance, higher maternal education reduced the risk of microcephaly prior to the pandemic in Brazil [ 128 , 129 ]. Further, lower household income and higher crowding was a risk factor for microcephaly [ 56 , 129 ]. Co-occurring health risks, such as malnutrition, increase the risk to the fetus [ 129 ].…”
Section: Public Health Community and Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, thousands of families of children with CZS continue to grapple with significant health and social consequences from the last epidemic. Children with CZS have been observed to experience a vast range of clinical manifestations, including dysphagia,14 hearing and visual abnormalities,15 16 early epilepsy,17 neurodevelopmental delays,18 19 adenoid hypertrophy,20 cryptorchidism,21 22 endocrine dysfunction23 and an estimated case fatality rate of 10% 24…”
Section: Introductionmentioning
confidence: 99%